AN EARLY ANALYSIS ON THE POSITION AND IMPLEMENTATION OF THE AUTHORITATIVE STATEMENT OF THE SHAFI‘ITE MADHHAB IN THE ECONOMIC LEGAL RULING STATE OF KEDAH AND STATE OF PENANG - Mohd Akram bin Dahaman@Dahlan; Kamarudin bin Ahmad; Solahuddin bin Abdul Hamid; Mohd Murshidi bin Mohd Noor (Journal of Islamic, Social, Economics and Development, 2018)
The authoritative statement of the Shafi‘ite madhhab in the state Islamic religiouslaw has been the basis of a very popular approach among fatwa-authorized bodies in Malaysia.Among the states that laid the foundations of a fatwa based on this approach were the state ofKedah and Penang. There are many fatwas that have been decided in these two states byinvolving various issues such as faith, worship, marriage, muamalat / economic, social andothers. Based on this, a preliminary analysis was undertaken to examine clearly the position ofThe aauthoritative statement of the Shafi‘ite madhhab and its implementation in fatwa affairsin both states, Kedah and Penang. At the same time, the study also examines the views of otherschool of thought that have been used to prescribe a fatwa. The results of this initial analysisshow the actual situation of the authoritative statement of the Shafi‘ite madhhab in the fatwaauthorized body of the state of Kedah and Penang. The study also explains the position of otherschools of thought in the fatwa in both states. Through the analysis of the fatwa text has yieldedsome clear indication of the basic implementation of The authoritative statement of the Shafi‘itemadhhab in the course of fatwa fixing on various issues arising and formulated.